Hydrogen-rich water irrigation enhances fruit quality in ‘Flame Seedless’ grapes by regulating chlorophyll fluorescence parameters and antioxidant activities - Ali, Hossam Salah Mahmoud; Zhang, Huanhuan; Yao, Dongdong; Kun, Liu; Zhao, Fengyun; Feng, Jianrong; Yu, Kun (Frontiers in Plant Science, 2025)
IntroductionHydrogen-rich water (HRW) plays a crucial role in regulating plant growth and development. However, its potential involvement in modulating photosynthetic pigments, chlorophyll fluorescence (ChlF) parameters, antioxidant enzyme activities, and fruit ripening in (Vitis vinifera L.) ‘Flame Seedless’ grapes grown in a greenhouse remain unclear.MethodsThis study aimed to investigate the effects of HRW irrigation at a concentration of 1.0 mg L-1 on chlorophyll pigments, ChlF parameters, enzymatic antioxidant activities, and fruit quality.ResultsHRW irrigation induced a significant increase in carotenoid (Car) content, which was observed only on the first day after irrigation. It also significantly enhanced chlorophyll a (Chl a) and chlorophyll b (Chl b) contents, as well as ChlF parameters such as maximum quantum efficiency of photosystem II (Fv/Fm), and the photochemical quantum yield of PSII (ΦPSII), while non-photochemical quenching (NPQ) decreased, indicating enhanced PSII functionality and photosynthetic performance. Antioxidant enzyme activities, including superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT), were also enhanced, reducing reactive oxygen species (ROS) accumulation and maintaining ROS homeostasis in grapevine leaves. HRW treatment promoted the accumulation of secondary metabolites such as total phenolic content (TPC), total flavonoid content (TFC), total anthocyanin content (TAC), and Car, which contributed to an improved color index of red grapes (CIRG). Additionally, fruit quality was improved by increasing total soluble solids (TSS), soluble sugars, and pH, while reducing fruit firmness and titratable acidity (TA). Berry weight and overall yield were also enhanced compared with control plants.DiscussionThese results demonstrate that HRW is a promising and sustainable approach for enhancing photosynthetic performance, antioxidant defense, secondary metabolite accumulation, and fruit quality in greenhouse-grown ‘Flame Seedless’ grapes, providing a practical basis for improving grape cultivation and production.